The Impact of the Chemical Engineering Faculty's Research Activity at Universidad Pontificia Bolivariana: A Bibliometric Analysis - Gañán-Rojo, Piedad; Barajas-Gamboa, Jaime; Forero-Gaviria, Luis A.; Castrillón-Hernández, Fabio (Journal of Engineering Education Transformations, 2025)
The Chemical Engineering Program at Universidad Pontificia Bolivariana (UPB) in Colombia will celebrate its 85th anniversary in 2023. This program is one of the oldest in the South American region. To commemorate the occasion, this work uses the bibliometric analysis and mapping tools to examine the evolution of the Faculty members' scientific output through time. 686 documents were analyzed in this work. Quantitative analysis enabled the identification of national and international cooperation, as well as preferred and most referenced journals. The evolution of trendy themes was determined by analyzing the authors ´keywords. The results reveal that Faculty teachers have been working on the most important subjects over time, cooperating with academics from 25 countries. The highest participation of female coauthors in at least 79% of the documents, as well as co-authorship with research from non-academic institutions that includes industry, are notable findings. This work contributes to recognizing the impact and relevance of the Chemical Engineering Program in Colombian society, as well as encouraging other writers around the world to assess the impact and contribution of their programs to societal development using tools such as bibliometric analysis.